Radiotherapy is an independent prognostic marker of favorable prognosis in non‐small cell lung cancer patients after treatment with the immune checkpoint inhibitor, nivolumab - Ou Yamaguchi; Kyoichi Kaira; Kosuke Hashimoto; Atsuto Mouri; Yu Miura; Ayako Shiono; Fuyumi Nishihara; Yoshitake Murayama; Shin‐ei Noda; Shingo Kato; Kunihiko Kobayashi; Hiroshi Kagamu (Thoracic Cancer, 2019)
Background It remains unclear why radiation clinically provides a synergistic effect when combined with immune checkpoint inhibitors such as nivolumab. The purpose of our study was to retrospectively evaluate whether the therapeutic efficacy of nivolumab is improved as a result of a history of radiotherapy (RT) in patients with previously treated advanced non‐small cell lung cancer (NSCLC). Methods From February 2016 to December 2017, 124 consecutive patients were administered nivolumab for pretreated advanced NSCLC. The patients were divided into RT and non‐RT groups. Results Sixty‐six (53%) of the 124 patients had been administered RT before the initiation of nivolumab, 52 (42%) received extracranial RT, and 40 (32%) were treated with thoracic RT. The median number of nivolumab cycles was 4 (range: 1–43). The overall response rate (ORR) and disease control rate (DCR) of nivolumab in all patients were 28.0% and 58.4%, respectively. The ORR (36.4%) was significantly higher in patients who had received previous RT than in patients who had not received any RT (19%). The therapeutic efficacy of nivolumab was particularly noteworthy in patients with non‐adenocarcinoma and squamous cell carcinoma histology administered extracranial RT, with ORRs of 48.3% and 52.6%, and DCRs of 87.1% and 84.2%, respectively. Conclusion Previous RT was an independent prognostic marker of favorable prognosis after nivolumab administration and improved the response rate to nivolumab treatment. Previous RT was clinically identified to have a synergistic effect with nivolumab treatment, increasing the response rate and improving the outcome of patients with advanced NSCLC.